2021
DOI: 10.15226/sojmid/8/1/001109
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Manifestations, Clinical Characteristics and Outcomes of COVID-19 in Adult and Pediatric Patients

Abstract: Background: Italy was the first country in Europe to report a SARS-CoV-2 case. Since then, the country has suffered a large number of COVID-19 infections both in adults and children. This disease has been shown to lead to different outcomes in these two groups, which oftenpresent varying symptoms and comorbidities. Aim: Therefore, we aimed to evaluate the symptoms, comorbidities and laboratory values in adults and children. Methods: We present the characteristics of 1,324 adults and 563 pediatric COVID-19 Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
(40 reference statements)
2
5
0
Order By: Relevance
“…In these case series, the level of reported fever among symptomatic children with COVID-19 was in the range of 69–78% and a cough was reported in 36–67% of cases. Compared to adult populations, children in our study reported lower frequency for most symptoms, which was also in line with other studies comparing frequency of symptoms among children and adults [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In these case series, the level of reported fever among symptomatic children with COVID-19 was in the range of 69–78% and a cough was reported in 36–67% of cases. Compared to adult populations, children in our study reported lower frequency for most symptoms, which was also in line with other studies comparing frequency of symptoms among children and adults [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Children are more likely to be asymptomatic or to have a mild COVID-19 infection compared to adults—as is supported by our study findings [ 39 , 40 ]; however, children face a similar risk of being infected with COVID-19 [ 49 ]. Our study found that young children, female children, and non-national children were less likely to be tested for COVID-19 using RT-PCR testing.…”
Section: Discussionsupporting
confidence: 84%
“…The emergence of the COVID-19 pandemic caused by the novel coronavirus, SARS-CoV-2, has evolved into a global health crisis. Initially focused on respiratory symptoms, it's now clear that COVID-19 presents a complex clinical picture affecting various organ systems 32 , 33 . Neurological manifestations have gained attention for their potential impact on both immediate clinical care and long-term health outcomes 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus is one of the common viruses that can cause acute gastroenteritis in children, especially in those younger than five years [ 1 , 2 , 3 ]. Rotaviruses are non-enveloped double-stranded RNA viruses that contain 11 segments and are classified into seven serogroups (A to G) and two sub-groups (I or II) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These viruses are further classified based on the antigenicity of the inner capsid protein (VP6). Group A rotaviruses are the most common causes of infections in children and are further subdivided into several genotypes based on the outer capsid glycoprotein VP7 (G-type) and VP4 (P-type) [ 1 , 2 , 3 , 4 ]. Although vaccination has decreased the prevalence of Group A rotavirus infections in South Korea, since 2000, Group A strains with the G4P and G8P genotypes have been predominant in children younger than 12 months in group outbreaks [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%